PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN CV.PASTI JAYA - Dian Suprapti, 14.05.51.0141; Wuryan, Sophiyanto (Students' Journal of Economic and Management, 2018)
The purpose of this research is to analyze the influence of each variable of quality of service, product quality and price perception to customer satisfaction CV Pasti Jaya. Population in this research is buyer of CV Pasti Jaya. The sample in this study used random sampling. Data analysis technique used is multiple linear regression analysis and hypothesis test. The results of the analysis can be concluded, that: quality of service has a significant effect on the customer satisfaction of CV Pasti Jaya. Product quality has a significant effect on the customer satisfaction of CV Pasti Jaya. Price perceptions have a significant effect on the customer satisfaction of CV Pasti Jaya.Keywords: quality of services, quality product, price perception, and customer satisfaction